Complementary combination of multiplex high‐throughput DNA sequencing for molecular phylogeny. Issue 1 (7th October 2021) - Suyama, Yoshihisa; Hirota, Shun K.; Matsuo, Ayumi; Tsunamoto, Yoshihiro; Mitsuyuki, Chika; Shimura, Atsuki; Okano, Kunihiro
Abstract: The rapid development of DNA sequencing technology in recent years has provided new tools for phylogenetic data acquisition. By using high‐throughput DNA sequencing technology, molecular phylogenetic information can be obtained more quickly and economically. Here, we describe a complementary combination of two multiplex high‐throughput DNA sequencing methods. One is multiplexed phylogenetic marker sequencing (MPM‐seq), and the other is multiplexed inter‐simple sequence repeat (ISSR) genotyping by sequencing (MIG‐seq), whose protocol is improved over that of the original one. Both MPM‐seq and MIG‐seq begin with multiplex polymerase chain reaction (PCR), each amplifying multiple phylogenetic markers and genome‐wide ISSR regions, respectively. After another PCR using a second PCR primer set that is common in both methods, next‐generation sequencing is used to simultaneously detect DNA sequences of multiple regions from multiple samples in each method. In this case study, we performed a molecular phylogenetic analysis of Japanese fir ( Abies ) and the closely related Abies species. MPM‐seq revealed DNA sequences of three regions from chloroplast DNA and one nuclear internal transcribed spacer and created a partially informative phylogenetic tree for 13 Abies species. Whereas MIG‐seq detected 6700 single‐nucleotide polymorphisms and exhibited clear clustering of related species with 97%–100% bootstrap support for all branches of the phylogenetic tree. Hence, with a complementary combination, quick, simple, and economical analysis can be performed in a wide range of genomic studies, including molecular phylogeny, as well as for investigating genetic differentiation or genetic identification among species, hybrids, and populations, and even among clones and cultivars, as a DNA barcoding technique. Abstract : As a complementary combination of two multiplex high‐throughput DNA sequencing methods, an overview of MPM‐seq and MIG‐seq methods was described in this case study, showing that they provide noteworthy information in the molecular phylogenetic analysis of Japanese Abies and the closely related Abies species. Here, we recommend a new approach for a quick, simple, informative, and economical analysis to be applied in a wide range of genomic studies.